Dialogando en los foros de discusión: pautas para el diseño y la evaluación - Sotomayor Zambrano, Manuel (2015)
The contemporary education, based on the psychological rediscoveries (Vygotsky, Freud) and on the philosophy of the mind (Wittgenstein, Austin), revalues the Social’s fundamental role in the mind develop of the human being. We center this paper on two aspects. The first one refers on how we can conceive the discussion forums as an educative tool (Internet tool) within the communication frame as one of the mechanisms by which the human beings build a common shared intersubjective space. The second aspect shows a criteria proposal (interactivity, dialogical cooperation and argumentative quality) that helps to evaluate if this educative tool develops the necessary conditions to improve dialogue.